Encrypted Thermal Printing with Regionalization Transformation - Hu, Run; Huang, Shiyao; Wang, Meng; Luo, Xiaobing; Shiomi, Junichiro; Qiu, Cheng‐Wei (Advanced materials (Weinheim), 2019)
Artificially structured thermal metamaterials provide an unprecedented possibility of molding heat flow that is drastically distinct from the conventional heat diffusion in naturally conductive materials. The Laplacian nature of heat conduction makes the transformation thermotics, as a design principle for thermal metadevices, compatible with transformation optics. Various functional thermal devices, such as thermal cloaks, concentrators, and rotators, have been successfully demonstrated. How far can it possible go beyond just realizing a heat‐distribution function in a thermal metadevice? Herein, the concept of encrypted thermal printing is proposed and experimentally validated, which could conceal encrypted information under natural light and present static or dynamic messages in an infrared image. Regionalization transformation is developed for structuring thermal metamaterial‐strokes as infrared signatures, enabling letters of the alphabet to be written, paintings to be drawn, movies to be made, and information to be displayed. This strategy successfully demonstrates an extreme level of manipulation of heat flow for encryption, illusions, and messaging. Heat conduction has long been considered in an omnidirectional diffusive way. Such a stereotype is successfully broken in this work and extreme heat flow manipulation is achieved, based on which encrypted thermal printing and regionalization transformation for structuring thermal metamaterial‐strokes as infrared signatures are proposed, enabling the writing of letters, the drawing of paintings, and the display of information.